People like you and me: the texts of Rosario Castellanos in the ideological contradictions of indigenist language policy - Ayala Reyes, Susana (Historia y Memoria de la Educación, 2021)
In this article we analyze documents written by Rosario Castellanos during the years that she worked as a scriptwriter for the puppet plays in the Highlands of Chiapas. These plays were part of educational campaigns aimed at the Tsotsil and Tseltal Maya population. We show that the discourses circulating during the years in which indigenous politics was being constructed were permeated by opposing and contradictory ideological tensions, tensions that were reflected in the proposal and use of categories of identification of the population and their languages, in the theoretical objectives and ideals and in the participants’ personal and collective stories.